2020
DOI: 10.13106/jafeb.2020.vol7.no9.409
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Foreign Ownership and Management on Firm Performance in Vietnam

Abstract: The human and capital resources from foreign investors are important sources of finance for developing countries. Foreign ownership can help the firm to raise funds for operations and the foreign management can help the firm expand the market and improve management. However, does this really happen to Vietnamese firm? To find the answer to that question, this paper examines the impact of foreign ownership and management on the financial performance of listed firms on Vietnam's stock market. The data collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
3
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 25 publications
1
27
3
6
Order By: Relevance
“…Using ROA and sales growth, the results regarding the influence of liquidity on these variables have not been consistent. If on the one hand, some authors find empirical evidence for a positive relationship (Nguyen and Nguyen, 2020 or Tahir et al , 2020), others show a negative relationship (Fuertes-Callén and Cuellar-Fernández, 2019; Nguyen et al , 2020 or Roy et al , 2019).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Using ROA and sales growth, the results regarding the influence of liquidity on these variables have not been consistent. If on the one hand, some authors find empirical evidence for a positive relationship (Nguyen and Nguyen, 2020 or Tahir et al , 2020), others show a negative relationship (Fuertes-Callén and Cuellar-Fernández, 2019; Nguyen et al , 2020 or Roy et al , 2019).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Tailab (2014) argued there is a positive association between growth rate and FP (Tobin's Q and ROA). Nguyen et al (2020) empirically proved that tangibility (Tang) and FP have a negative association, which is quite similar to ROA and Tobin's Q. Muzir (2011) found out that ROA and tangibility have a positive association.…”
Section: Theoretical Background and Previous Literaturementioning
confidence: 74%
“…In their study, Almajali and Shamsuddin (2019) reported that liquidity (LIQ) has a positive effect on financial performance. Nguyen et al (2020) and Sadeghian et al (2012) found out a negative significant association between liquidity and FP, proxies by ROA and Tobin's Q.…”
Section: Theoretical Background and Previous Literaturementioning
confidence: 95%
“…Investor asing, cenderung menjadi investor yang kurang informasi dan berasal dari rezim yang lebih transparan mungkin menuntut pengungkapan informasi keuangan yang tinggi dibandingkan dengan investor lokal yang lebih terinformasi dan mungkin dapat mengakses informasi keuangan yang mereka butuhkan (Mohammed, 2018). Kepemilikan asing sendiri memiliki cara pengukuran dengan membandingkan jumlah saham dari investor saham dengan jumlah keseluruhan saham yang bereda (Hong Nguyen et al, 2020).…”
Section: Foreign Ownershipunclassified
“…Hasil penelitian dari (Mertzanis, Basuony and Mohamed, 2019) melihat adanya variabel kontrol yaitu ukuran perusahaan berpengaruh negative terhadap kinerja perusahaan. Sedangkan hasil penelitian dari (Amin and Hamdan, 2018;Hong Nguyen et al, 2020), (Al-Janadi, 2021) dan (Kao, Hodgkinson and Jaafar, 2019) memaparkan bahwa variabel kepemilikan asing memiliki hubungan positif atau mempengaruhi secara positif terhadap kinerja perusahaan.…”
Section: Kerangka Konseptualunclassified